If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 7(2x + 9) = 3x + 100 Reorder the terms: 7(9 + 2x) = 3x + 100 (9 * 7 + 2x * 7) = 3x + 100 (63 + 14x) = 3x + 100 Reorder the terms: 63 + 14x = 100 + 3x Solving 63 + 14x = 100 + 3x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-3x' to each side of the equation. 63 + 14x + -3x = 100 + 3x + -3x Combine like terms: 14x + -3x = 11x 63 + 11x = 100 + 3x + -3x Combine like terms: 3x + -3x = 0 63 + 11x = 100 + 0 63 + 11x = 100 Add '-63' to each side of the equation. 63 + -63 + 11x = 100 + -63 Combine like terms: 63 + -63 = 0 0 + 11x = 100 + -63 11x = 100 + -63 Combine like terms: 100 + -63 = 37 11x = 37 Divide each side by '11'. x = 3.363636364 Simplifying x = 3.363636364
| 6+3*5-2=18 | | 5(3x-6)=12 | | 19=23-2v | | -2(4x-2)+6x=4(x+3) | | 4m-9= | | 6+3*5-2=5 | | 2(3x+2)+6(2x-1)=40 | | 13x-4=2x+4 | | -72=-8(4-2x)-8(1-2x) | | 13x-4=2x+2 | | 2p=96-10 | | 5p-7p=3p+1 | | 13x+4=-5x+1 | | -86=-2(1-6a) | | 6sqrtx=x | | -5(-3v+5)-8v=3(v-5)-4 | | 13x+4=-5x-3 | | 2m+3m=4m-9 | | 4(2x-5)=43 | | -37=-3(1+6m)-2(m+7) | | 3m^3-15m^2+75m=0 | | x^2+y^2-22x+112=0 | | 2b-5b=-9 | | (2x-1)/4+(3x+4)/8=(1-4x)/12 | | 3(z+3)=2(z+8) | | 31=5x+5x-9 | | 9-ln(4-x)=0 | | 4x=-5+2x+18 | | -2(-9w+1)-2w=2(w-1)-2 | | 2x+13=5x-14 | | 5y=2(y+6) | | -5w+3(w-5)=-13 |